Internet connectivity disruption in PF (French Polynesia) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity disruption detected in French Polynesia. Data sourced from IODA.
Network Disruption Incident ID: PF-2026-0001. Severity: critical. Confidence: 65%